2021
DOI: 10.1049/cth2.12083
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical global fast terminal sliding‐mode control for a bridge travelling crane system

Abstract: The bridge crane system is a typical under‐actuated system that is widely used in production and life. Although various scholars have conducted extensive research on the bridge crane system in recent years, there are still many problems, such as the trajectory planning of the cart and the anti‐sway control of the cargo. In order to tackle the problem of the anti‐sway control of the cargo, a hierarchical global fast terminal sliding‐mode control (H‐GFTSMC) is developed in this work. First, the Lagrange equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Yang, W.L. [17] combined hierarchical sliding mode control and terminal sliding mode control to design a hierarchical global terminal sliding mode controller, and the simulation results showed that the load swing angle of the bridge crane system would converge asymptotically. All of the aforementioned control methods enable the bridge crane system to position and anti-sway.…”
Section: Introductionmentioning
confidence: 99%
“…Yang, W.L. [17] combined hierarchical sliding mode control and terminal sliding mode control to design a hierarchical global terminal sliding mode controller, and the simulation results showed that the load swing angle of the bridge crane system would converge asymptotically. All of the aforementioned control methods enable the bridge crane system to position and anti-sway.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the linear sliding mode (LSM) [4] can only achieve the asymptotic stability of a system. Consequently, fast terminal sliding-mode control (FTSMC) [5], which was predicated on the concept of terminal attractors, was developed. Although the FTSMC scheme has a fast convergence rate and limited time stability, it still has singularity.…”
Section: Introductionmentioning
confidence: 99%
“…The associate editor coordinating the review of this manuscript and approving it for publication was Azwirman Gusrialdi . sliding mode control [3], [4], predictive control [5], [6], active disturbance rejection control [7], [8], robust control [9], [10] and other control methods. In [4], a hierarchical global fast terminal sliding mode control is designed to reduce the disturbance of rope length change and system uncertainty on the control performance, and the simulation results show that the control method can achieve good trolley positioning and load anti-swing control.…”
Section: Introductionmentioning
confidence: 99%
“…sliding mode control [3], [4], predictive control [5], [6], active disturbance rejection control [7], [8], robust control [9], [10] and other control methods. In [4], a hierarchical global fast terminal sliding mode control is designed to reduce the disturbance of rope length change and system uncertainty on the control performance, and the simulation results show that the control method can achieve good trolley positioning and load anti-swing control. Reference [6] proposes a novel control approach based on a multivariable model predictive control and a particle swarm optimizer for limiting the transient and residual swing of a payload transferred by an overhead crane and the experimental research proves the effectiveness of the control method.…”
Section: Introductionmentioning
confidence: 99%